FeIn2S4 Nanocrystals: A Ternary Metal Chalcogenide Material for Ambipolar Field‐Effect Transistors. Issue 7 (27th March 2018) - Kim, Hyunjung; Tiwari, Anand P.; Hwang, Eunhee; Cho, Yunhee; Hwang, Heemin; Bak, Sora; Hong, Yeseul; Lee, Hyoyoung
Abstract: An ambipolar channel layer material is required to realize the potential benefits of ambipolar complementary metal–oxide–semiconductor field‐effect transistors, namely their compact and efficient nature, reduced reverse power dissipation, and possible applicability to highly integrated circuits. Here, a ternary metal chalcogenide nanocrystal material, FeIn2 S4, is introduced as a solution‐processable ambipolar channel material for field‐effect transistors (FETs). The highest occupied molecular orbital and the lowest unoccupied molecular orbital of the FeIn2 S4 nanocrystals are determined to be −5.2 and −3.75 eV, respectively, based upon cyclic voltammetry, X‐ray photoelectron spectroscopy, and diffraction reflectance spectroscopy analyses. An ambipolar FeIn2 S4 FET is successfully fabricated with Au electrodes ( E F = −5.1 eV), showing both electron mobility (14.96 cm 2 V −1 s −1 ) and hole mobility (9.15 cm 2 V −1 s −1 ) in a single channel layer, with an on/off current ratio of 10 5 . This suggests that FeIn2 S4 nanocrystals may be a promising alternative semiconducting material for next‐generation integrated circuit development. Abstract : An ambipolar transistor is demonstrated by using FeIn2 S4 nanocrystals based on studies for band structures of ternary metal chalcogenide material, namely FeIn2 S4 . Its band edges are first reported as E C = −3.75 eV and E V = −5.1 eV, which can provide both electron and hole transport behavior within single channel layer in field‐effect transistors.